TOTAL MICROBIAL PLATES ON BEEF AND BEEF OFFAL - Sukmawati Sukmawati (UNIVERSITAS NEGERI PADANG, 2018)
Efforts to improve people’s nutritional health can be obtained through nutritional food. Beef is a source of animal protein needed. But foodstuffs such as meat and eggs other than as a source of protein is also one of the microorganisms breeding media, which can be a type of human disease. The aim this study was to find out whether the sample of beef, beef heart, and beef liver are safe to consume and marketable. This research method includes tool sterilization, microbial growth medium, and the analysis phase used total plate count method. Samples of beef number of microbial colonies as much as 660 cells/ml. samples of cow’s heart contained colonies 3.150 cells/ml, and in liver samples there are 3.000 cells/ml. so it can be concluded that beef and dairy products are feasible to marketable and to consumption. Keywords: Total Microbial, Beef, Beef Offal